Implementasi Framework ITIL v3 Domain Service Strategy Dalam Perancangan Layanan Helpdesk Pada Jurusan Administrasi Bisnis Politeknik Negeri Sriwijaya - Bangga Surya Nagara; Tata Sutabri (Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2023)
Improving service efficiency and system management has become a major focus in the higher education environment, especially in the context of helpdesk services. This research explores the application of ITIL v3 (Information Technology Infrastructure Library) Framework in the development of helpdesk services at the Business Administration Department at Politeknik Negeri Sriwijaya. The research method used is a qualitative approach with in-depth interviews with IT staff, lecturers, and students. The analysis results highlight the implementation of ITIL v3 modules such as change management, capacity management, and service management as a foundation for improving the quality of helpdesk services. The implementation of ITIL v3 Framework has brought significant impact in improving service responsiveness, reliability, and efficiency. The results of this study provide an in-depth understanding of the benefits of implementing the ITIL v3 Framework in the context of higher education, especially in the Business Administration department at Politeknik Negeri Sriwijaya.